2020
DOI: 10.1177/0018720820974856
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vehicle Automation on Driver Engagement: The Case of Adaptive Cruise Control and Mind Wandering

Abstract: Objective This field study examined the effects of adaptive cruise control (ACC) on mind wandering prevalence. Background ACC relieves the driver of the need to regulate vehicle speed and following distance, which may result in safety benefits. However, if ACC reduces the amount of attentional resources drivers must devote to driving, then drivers who use ACC may experience increased periods of mind wandering, which could reduce safety. Methods Participants drove a prescribed route on a public road twice, once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Stephenson et al also explored older adults' autonomic arousal and found that safety-critical events (such as TORs) may narrow their visual attention and elevate arousal mechanisms (Stephenson et al, 2020). Furthermore, increasing the level of automation does not seem to decrease driving performance; on the contrary, it may even provide a safer drive among drivers with limited experience with the technology (Weaver et al, 2020).…”
Section: Related Work On To Quality Aspectsmentioning
confidence: 99%
“…Stephenson et al also explored older adults' autonomic arousal and found that safety-critical events (such as TORs) may narrow their visual attention and elevate arousal mechanisms (Stephenson et al, 2020). Furthermore, increasing the level of automation does not seem to decrease driving performance; on the contrary, it may even provide a safer drive among drivers with limited experience with the technology (Weaver et al, 2020).…”
Section: Related Work On To Quality Aspectsmentioning
confidence: 99%
“…Lohani et al (2021) found a similar null effect of automation on physiological arousal, as measured by heart rate and heart rate variability. Furthermore, Weaver et al (2022) periodically probed drivers and found a null effect of automation on self-reported mind wandering, physiological arousal, and driving performance. These results suggest there may be a difference between simulated and real driving, such that the potential for deadly consequences on real roadways forces drivers to remain engaged in a way that is not captured in simulated driving, where poor driving performance is less consequential.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that drivers with no prior automation experience (such as those in Lohani et al, 2021, McDonnell et al, 2021b; Weaver et al, 2022) remain engaged due to the novelty of the technology. Evidence suggests that increased familiarity with automation leads to increases in trust and decreases in stress over time (Endsley, 2017b; Gaspar & Carney, 2019).…”
Section: Introductionmentioning
confidence: 99%